Horizontal orientation facilitates pollen transfer and rain damage avoidance in actinomorphic flowers of Platycodon grandiflorus. (15th March 2022) - Nakata, T.; Rin, I.; Yaida, Y. A.; Ushimaru, A.
ABSTRACT: In zoophilous plants, floral orientation evolved under both biotic and abiotic pressure to enhance pollination success. However, the adaptive significance of horizontal orientation in radially symmetrical (actinomorphic) flowers remains largely unknown, although that of bilaterally symmetrical flowers has been well studied. We experimentally altered floral angle in a population of insect‐pollinated Platycodon grandiflorus flowers to examine the effects of floral orientation on pollinator behaviour, pollination success and pollen rain damage avoidance. To further investigate the potential pollen damage by rain, we obtained past precipitation records for the study area during the flowering season, and experimentally tested P . grandiflorus pollen damage by water. Horizontally oriented flowers received more pollinator visits and had pollen grains on the stigma in male and/or female phases than downward‐ and/or upward‐oriented flowers and avoided pollen damage by rainfall better than upward‐oriented flowers. A pollen germination experiment showed that approximately 30% of pollen grains burst in distilled water, indicating that pollen damage by rainfall may be significant in P . grandiflorus . Our field experiments revealed that upward‐oriented flowers cannot avoid pollen damage by rainfall during the flowering period, and that both upward‐ and downward‐oriented flowers experience pollinator limitation in female success. Therefore, horizontal flower orientation appears to be adaptive in this insect‐pollinated actinomorphic species that blooms during the rainy season. Abstract : Horizontally oriented flowers can avoid rain damage and have high pollen transfer success in actinomorphic species Platycodon grandiflorus .